Near‐inertial kinetic energy budget of the mixed layer and shear evolution in the transition layer in the Arabian Sea during the monsoons. Issue 9 (26th September 2015) - Majumder, Sudip; Tandon, Amit; Rudnick, Daniel L.; Thomas Farrar, J.
Abstract We present the horizontal kinetic energy (KE) balance of near‐inertial currents in the mixed layer and explain shear evolution in the transition layer using observations from a mooring at 15.26° N in the Arabian Sea during the southwest monsoon. The highly sheared and stratified transition layer at the mixed‐layer base varies between 5 m and 35 m and correlates negatively with the wind stress. Results from the mixed layer near‐inertial KE (NIKE) balance suggest that wind energy at times can energize the transition layer and at other times is fully utilized within the mixed layer. A simple two layer model is utilized to study the shear evolution in the transition layer and shown to match well with observations. The shear production in this model arises from alignment of wind stress and shear. Although the winds are unidirectional during the monsoon, the shear in the transition layer is predominantly near‐inertial. The near‐inertial shear bursts in the observations show the same phasing and magnitude at near‐inertial frequencies as the wind‐shear alignment term.